Comparative analysis of slotless and slot type Halbach array permanent magnet linear motor in robotic applications comparative analysis of slotless and slot type Halbach array permanent magnet linear motor in robotic applications - Mohamad Mokhtar, Faridahtun Akmalliah; Iqbal, A. K. M. Parvez; Mohamed Sahari, Khairul Salleh; Aris, Ishak (Universiti Tenaga Nasional, 2017)
This paper study the performance of a two different topology of permanent magnet linear motor with Halbach array. The motors were developed for robotic arm movement. These two topology are, slot less and slot-type linear motor have different designs but same in size and the stator core of both designs have employed same number of Halbach array. Based on finite element method (FEM), thrust force, displacement and magnetic flux in the both topologies have been established and compared. The simulation results indicate the effectiveness of the slot type linear motor to drive maximum linear thrust to the upper arm for robotic movement. After optimizing the obtained data, specifications of the linear motor have been selected for fabrication.